Virtual education and student perception of teacher performance in the distance learning environment - Richard Flores-Cáceres; Cesar León-Velarde; Teodoro Díaz-Leyva; Frank Escobedo-Bailón; Orlando Ortega-Galicio; Antuanet Chirinos-Mendoza; Abel Tasayco-Jala (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
This article aims to carry out a descriptive analysis of the performance of teachers qualified as researchers, in the distance education environment according to the student's perspective. The results will be a frame of reference for university authorities on the path of continuous improvement of virtual education. When carrying out the research, a general qualification of the teaching performance of 14.20 was determined, established the highest grade equal to 20, it can be indicated that there is a good performance of the teacher in the virtual education environment. In addition, the results show that the highest evaluation corresponds to the indicator management of the group and fulfillment of the objectives, which is directly related to the administration of the class, while the lowest rating is for the indicator "Teacher effectiveness so that their students acquire relevant knowledge, skills and attitudes”, which is directly related to the didactic strategies used, that is, to the use of technological tools that today are more than just an option. Finally, it can be noted that of the total of 17 teaching, 23.5% present a very good performance, 35.3% present a good performance and 41.2% present a regular performance.